Organisational metamorphosis: Tracing sustainability integration through sentiment evolution in corporate reporting in Turkish companies - Yavuz Selim Balcioglu; Abdullah Kürşat Merter (Amfiteatru Economic, 2025)
This study examines the evolution of sentiment in the sustainability reports of Turkish companies from 2014 to 2023, serving as an indicator of organisational change in response to shifting sustainability regulations. A longitudinal sample of corporate sustainability reports was subjected to sentiment analysis and linguistic pattern recognition, encompassing three distinct regulatory periods. By comparing the tone and language across these periods, the study investigates how companies adapt their sustainability communication strategies under increasing institutional pressures. The study is grounded in organisational change theories and regulatory response models. It sheds light on whether heightened disclosure requirements and global sustainability norms have driven substantive shifts in corporate narrative or merely superficial compliance. The analysis reveals notable changes in sentiment, with an overall trend toward more optimistic and assertive sustainability disclosures over time. These linguistic adaptations correspond to key regulatory milestones. The findings suggest a gradual internalisation of sustainability principles, reflecting organisational learning and strategic legitimisation efforts. The findings contribute to the extant literature on corporate sustainability reporting by linking textual sentiment trends to institutional change dynamics, offering a rare developing-country perspective. The insights are particularly relevant for stakeholders and policymakers seeking to understand and enhance the impact of sustainability reporting in emerging economies.
Keywords: M14; Q56; G38; 330; sustainability reporting; sentiment analysis; organisational change; institutionaltheory; ESG; legitimacy